ANALYSIS INTERNAL PRIMER OF GENES 16S RRNA ENDOPHYTIC BACTERIA PRODUCING COMPOUND ANTIMICROBIAL FOR SEQUENCING - dina vaniana; Dwi Hilda Putri (Universitas Negeri Padang, 2019)
Endophytic bacteria can produce active compounds that function as antitumor, antioxidant and antimicrobial. The steps taken can be done for the use of endophytic bacteria is identification of bacteria. Endophytic bacteria have a 16S rRNA gene. The most widely used technique for identification is DNA sequencing. For the sequencing process it takes a primer that can read 1500 bp sequences. The purpose of this study was to obtain primers who could read the internal area of the 16S rRNA gene and be able to be used in the sequencing process. This research uses BioEdit software and Primer Designer. The isolate used as a DNA template in the sequencing process is B.J.T.A.2.1. DNA template were amplified using the PCR method. The results of PCR products were analyzed using 1% agarose gel electrophoresis. The sequencing process is carried out with NIF (forward) and NIR (reverse) primers. The results showed that the primer could recognize the 16S rRNA internal region of the antimicrobial compound endophytic bacteria. Both primers are able to start the sequencing process and produce a sequence of 1130 bp. However, good sequence readings were only ± 100 bp due to contamination of DNA template.